The Effectiveness of Coaching for Improving Student Competence: A Literature Review - Isra Dewi Kuntary Ibrahim; Ni Wayan Adelia Mutiara Asri; Dinis Cahyaningrum; Tifany Dame Hasany; Dhanny Safitri (Sciences du Nord Economics and Business, 2026)
As the future leaders of the nation currently pursuing higher education, students actually seek knowledge, skills, experience, and a strong moral character. On BPS data, the percentage of young people (aged 15–24) who are neither in school, employed, nor enrolled in training—at 19.44% in 2025—remains relatively high, meaning approximately 1 in 5 young people in Indonesia have not yet gained access to quality education, and access to training as preparation for entering the workforce. Objective of systematic literature review (SLR) is to understand how coaching can tangibly enhance students’ competencies, as well as the factors that strengthen or weaken this relationship. SLR methodology, which involves the identification, evaluation, and interpretation of relevant research on the effectiveness of coaching methods to student competencies. The results indicate that coaching has a significant impact on improving student competencies. Coaching programs significantly enhance students’ knowledge, skills, and attitudes, which are described differently. In conclusion, coaching is effective in improving students’ academic and non-academic performance. Students become better at critical thinking, academic planning, and developing a reading culture. Coaching methods are also effective in fostering self-reflection. Higher education institutions should focus on appropriate methods for developing practical skills than interpersonal development.